Evaluation of Periodontal Status among Dental Students of Dow International Dental College, DUHS - Abrar, Syed Kashif; Kumar, Chander; Allana, Raheel; Siddiqui, Saad Uddin; Kumar, Lovekesh; Darvesh, Sajjad Ali (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To evaluate the periodontal status in dental students and to assess the knowledge and understanding of its management. Methodology: A cross sectional study was conducted on dental students of Dow International Dental College from October to November 2019 Karachi for the assessment of periodontal health. Sample size was calculated by Open epi with 95% confidence interval. Students were selected through non-probability sampling technique from batches of 3rd and 4th year. The data was collected from 80 students of Dow International Dental College, DUHS and the results have been classified into three groups i.e; Gingivitis, Periodontitis and Normal Healthy Periodontium using the criteria of clinical signs: presence of bleeding on probing and attachment loss of ?2 mm. All four surfaces (mesiofacial, midfacial, distofacial, and lingual) of all posterior teeth were examined. Students with bleeding on probing, gingival inflammation, tooth mobility, furcation involvement and attachment loss more than 3.5mm were assessed by taking OPG and periapical radiographs. A self-assisted periodontal form was filled for each student in which their medical and dental history was noted down. Results: A total of 80 students were examined in which 22 students (male =14; female =8) showed clinical sign of disease. This was a clear sign of students having periodontitis. It was also observed that 31 students were having gingivitis and 27 students showed normal healthy periodontium. Conclusion: The clinical students demonstrated a good amount of knowledge of disease and management despite having poor oral health in males as compared to females. Key words: Periodontitis, Gingivitis, Normal Healthy Periodontium